1988
DOI: 10.1111/j.1365-3024.1988.tb00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Toxocara ELISA in tropical populations

Abstract: The diagnosis of human infection by Toxocara canis relies heavily upon serological tests, the specificity of which can be inadequate in regions of endemic helminthiasis. When different population groups of tropical Venezuela were evaluated using ELISA based upon Toxocara excretory-secretory antigen (TcESA), solid-phase adsorption of the sera with extracts of a wide variety of non-homologous parasites revealed the existence of significant cross-reactivity. This was effectively and conveniently overcome when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
1
11

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 18 publications
2
57
1
11
Order By: Relevance
“…Protozoan and helminth infections have been found in similar population from other South America cities 5,7,10,23 . We also note that the presence of mixed infections between Toxocara and other helminths can contribute to increase the frequency of positivity using conventional serological tests, as the one of this study.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Protozoan and helminth infections have been found in similar population from other South America cities 5,7,10,23 . We also note that the presence of mixed infections between Toxocara and other helminths can contribute to increase the frequency of positivity using conventional serological tests, as the one of this study.…”
Section: Discussionmentioning
confidence: 74%
“…Many authors refer that the main cause of crossreactions in serological tests for immunodiagnostics of toxocariasis are the presence of other helminth infections, while protozoa and coccidia are less related 4,15,23,26 . In our study, we observed false positive reactions in sera from parasitized subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these antigens lacked sensitivity and expressed high degrees of cross reactivity with Ascaris and other geo-helminthes, such as S. stercoralis ancylostomids and T. trichiura 95 . Although the use of TES antigen has notably improved the efficiency of the test, this may not be specific enough when used in countries where this type of infection is prevalent 66,86 . Therefore, commercial "kits" that can not determine previous absorption of sera with antigens of these parasites can be of limited use in the diagnosis of toxocariasis in tropical countries.…”
Section: Elisamentioning
confidence: 99%
“…MAGNAVAL et al 67 used the WB technique to confirm positivity determined in human sera previously processed by the ELISA technique for IgG antibodies using antigen TES and achieved greater specificity with fractions of low molecular weight (24 to 35 kDa). The study by NUNES et al 78 , using the Immunoblot test, determined that the 55-66 kDa antigenic complex was responsible for the cross reactivity between T. canis and A. suum; whereas LYNCH et al 66 had stated that strong cross reactivity between these two ascarids occurred in the 81 kDa antigen. In Brazil, JACOB 56 conducted a sequential study of patients with VLM and after treatment, WB showed the disappearance of certain fractions of high molecular weight (97-116 and 200-210 kDa), a pattern that could represent the individual behavior of the immune response of the patient and may be related to the slow fall in titers observed in the ELISA.…”
Section: Immunoblottingmentioning
confidence: 99%
“…The test commonly employed for the serodiagnosis of toxocariasis is ELISA using Toxocara excretory-secretory (TES) antigens to detect serum anti-Toxocara IgG antibodies (De Savigny et al 1979, Jacquier et al 1991. However, some components of TES antigens are not specific, demonstrating moderate cross-reactivity with other helminth species (Speiser & Gottstein 1984, Lynch et al 1988, Jacquier et al 1991, Nunes et al 1997. Sera from patients with ascariasis, filariasis, schistosomiasis and strongyloidiasis also react with TES antigens (Maizels et al 1984, Nunes et al 1999, Yamasaki et al 2000.…”
mentioning
confidence: 99%